Characteristics of patients with anxiety disorder without selective serotonin reuptake inhibitor prescription over a two‐year period of pharmacotherapy - Keisuke Mori; Fumitoshi Kodaka; Arisa Yamamoto; Ryuichi Yamazaki; Junpei Ishii; Wataru Yamadera; Hisatsugu Miyata; Masahiro Shigeta (Wiley, 2024)
Abstract Introduction Pharmacotherapy such as selective serotonin reuptake inhibitors (SSRIs) or serotonin‐noradrenaline reuptake inhibitors is recommended for the treatment of anxiety disorders. Although there are patients with persisted symptoms of anxiety disorders who are treated with monotherapy of benzodiazepine anxiolytics without SSRIs, the characteristics of these patients are unclear. In the present study, we investigated the characteristics of patients with persisted symptoms of anxiety disorder without SSRI prescription. Methods From a prescription dataset covering 2018 and 2020, the prescriptions of 243 patients with anxiety disorder were analyzed. Patients were classified into two groups: SSRI non‐prescription and prescription groups. Results The SSRI non‐prescription group had a higher ratio of females than did the SSRI prescription group (60.1% vs. 44.6%, respectively, p = 3.12 × 10−2), but statistically not significant after the Bonferroni correction. No significant differences in age, body mass index, or duration of outpatient visits were found between groups. Among the independent variables, sex (female) was the only variable identified that predicted SSRI non‐prescription. Conclusion The present study showed that among patients with anxiety disorders, sex (female) was the only variable that predicted SSRI non‐prescription.